Digital innovation in water quality monitoring: Fishing for solutions - Mukuyu, Patience (CGIAR System Organization, 2022)
Deteriorating water quality is a global challenge, more so in surface waters. Traditional methods of monitoring water quality are human resource intensive and require the active involvement of technical personnel in remote environments. Nonetheless, it is essential to monitor water quality trends and to obtain baseline information on how water resources are being impacted over time by human activity – and how this can potentially affect socioeconomic development as well as human and ecological health.